The Digha Nikaya and its Commentaries. Dhammagiri-Pali-Ganthamala, Volumes 1-11. - Norman, K. R. (Buddhist Studies Review, 1997)
The Digha Nikaya and its Commentaries. Dhammagiri-Pali-Ganthamala, Volumes 1-11. Vipassana Research Institute, Igatpuri 1993-95.